2015
DOI: 10.1186/s12891-015-0572-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of various SYSADOA for the osteoarthritis treatment: an experimental study in rabbits

Abstract: BackgroundOsteoarthritis is thought to be the most prevalent chronic and disabling joint disease in animals and humans and its treatment is a major orthopaedic challenge because there is no ideal drug treatment to preserve joint structure and function, as well as to ameliorate the symptomatology of the disease. The aim of the present study was to assess, using histology, histomorphometry and micro-CT, the effects of the treatment with several drugs of the SYSADOA group and a bisphosphonate in a model of early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 63 publications
3
20
0
4
Order By: Relevance
“…Regarding histological synovial membrane assessment, we observed that risedronate administration did not present a significant efficacy in the pathological changes evaluated. However, we noticed a slightly anti-inflammatory activity as previously published in early stages of OA (24,60).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Regarding histological synovial membrane assessment, we observed that risedronate administration did not present a significant efficacy in the pathological changes evaluated. However, we noticed a slightly anti-inflammatory activity as previously published in early stages of OA (24,60).…”
Section: Discussionsupporting
confidence: 82%
“…Some authors observed an improved trabecular bone volume, number, and thickness with BP administration compared to those of untreated groups (13,14,19,23,65). In the specific case of risedronate, a positive effect was noted, preserving subchondral bone properties in short-term administrations in a rabbit model of OA (23,25,60). Nevertheless, in our case, risedronate administration did not seem to preserve trabecular bone mass, exhibited decrease in overall bone quality with loss of vBMD, a tendency to decrease BV/TV and Tb.N, and increase Tb.Sp.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the decrease in subchondral bone microarchitectural parameters was associated with demineralization, which suggests subchondral bone resorption, likely as a result of the effect of HA on osteoclast activity in OA subchondral bone [ 38 ]. On the contrary, in a rabbit model of OA, Permuy et al [ 21 ] did not observe any significant subchondral bone loss following HA intra-articular injection in a OA rabbit model [ 21 ]. This discrepancy might result from the more severe induction technic (combining ACLT and meniscectomy vs. ACLT) and the later endpoint used in their study (11 vs. 6 weeks) leading to a more advanced OA and thus to the recovery of initial subchondral bone microarchitectural parameters and mineral density [ 5 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Prince et al [ 18 ] observed in vivo osteoclast activation, leading to bone resorption. To date no clear action of HA has been depicted on bone and only few investigators have explored the effect of intra-articular HA injection on key determinants of subchondral bone microarchitecture and strength [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Результаты недавно опуб-ликованого исследования, проведенного на модели ОА у кроликов [6], показали, что лечение диацереином способно уменьшить отек и поверхностные изменения хряща, оказы-вает противовоспалительное действие на синовиальное вос-паление, а также анаболическое действие на субхондраль-ную губчатую кость. При сравнении с препаратами гиалуро-новой кислоты и хондроитина и глюкозамина сульфата от-мечено более значимое положительное влияние диацереина на воспалительный процесс в синовиальной оболочке и со-стояние субхондральной кости [7].…”
unclassified